Ameliorative Effect of Cow Urine Against Cisplatin Induced Nephrotoxicity in Rats - Gururaja, M.P.; Joshi, A.B.; Joshi, Himanshu (Asian Journal of Chemistry, 2010)
In this study, the nephroprotective activity of cow urine was undertaken. The effect of cow urine distillate was studied in vivo in rats intoxicated with cisplatin. The nephrotoxicity was induced with the administration of single i.p. dose of cisplatin 5 mg/kg body weight. The protective effect of cow urine distillate (in three dose levels) were studied in intoxicated rats. Parameters for the assessment of activity included kidney function tests and histological observations. The cow urine distillate produced dose dependent significant (p < 0.05) lowering of the elevated blood urea, serum creatinine and blood protein levels when compared with the toxic control. The presence of antioxidants in cow urine might cause the observed protective effects.